Радиоактивность и радиоактивные элементы в среде обитания человека - Рихванов Л. П. Леонид Петрович; Арбузов С. И. Сергей Иванович; Архангельская Т. А. Татьяна Александровна; Барановская Н. В. Наталья Владимировна; Беляева А. М.; Волостнов А. В. Александр Валерьевич; Язиков Е. Г. Егор Григорьевич (2006, 2006)
В фонде НТБ ТПУ отсутствует